Penggunaan Alih Kode bagi Santri Baru di Pondok Pesantren Ulil Albaab Melalui Pengajaran Tutor Sebaya Tahun 2020 - Baiq Yulia Kurnia Wahidah; Alpan Ahmadi (Peneliti.net, 2020)
This study discusses the use of code switching for new students at the Ulil Albaab Islamic boarding school when conducting peer tutoring. The peer tutoring lasts for six months running. The students conduct peer tutoring by learning two foreign languages, namely Arabic and English. The sample of this study was the new students in the Ulil Albaab boarding school. The method of this research is the method of tapping and documentation. Thus, the data that will be obtained is in the form of vocabulary, sentences that contain the use of code switching during peer tutoring. Data analysis using descriptive qualitative. The result of this research is finding the use of code switching by students from three languages, namely Indonesian, Arabic, and English.